Interpretive Subjectivity and Gender Relativism in the Theories of Postmodernism - Vlasova, Tatyana I.; Martseniuk, Larysa V. (Національний педагогічний університет ім. М. П. Драгоманова, м. Київ, 2019)
ENG: Interpretation as a stream of our consciousness is determined by dierent contexts and various narratives which stimulate this process reacting to the changeability of the world and human beings in it. The postmodern theory while losing its topicality keeps the key principle of interpretationrm and stable. Interpretation is simultaneously open and fixed, though the process of constructing narratives is not. As interpretation provides vast space for gender, the feminist theory proceeds with the «new feminist reading», and the aim of the feminist criticism lies in revealing misogynism and masculine approaches to dierent discourses and narratives. Still in postmodernism feminist interpretation often rejects «comprehension» in its classical meaning denying analogy, symmetry and equivalence. The subjectivity of feminist interpretation is not a transparent line between the human being and the surrounding world: the «better» is interpretation, the more «objective» seem our narratives, the stronger appear constructs stipulated by culture, gender, ideology.
Інтерпретативна суб'єктивність і гендерний релятивізм в теоріях постмодернізму
T. Vlasova: Orcid 0000-0001-5040-5733; L. Martseniuk: ORCID 0000-0003-4121-8826
Keywords: narrative; changeability; feminism; concept; translation; construct; КФП; КЕМ